Aerial surveys of Greater White-fronted Geese Anser albifrons frontalis and other waterfowl in the Rasmussen Lowlands of the Central Canadian Arctic. - Hines, J E; Kay, M F; Wiebe, M D (Wildfowl, 2013)
x.